Transformasi Palembang Menuju Kota Multikultural: Sebuah Refleksi terhadap Naskah Undang-Undang Simbur Cahaya dan Tuhfah ar-Raghibin - Wirajaya, Asep Yudha (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
History has recorded Palembang as a multiethnic city capable of developing into the capital of the Maritime kingdom. Of course, this success can not be separated from the participation of leaders and stakeholders who have struggled for their vision to be achieved. This is reflected in the text "The Law of the Simbur of Light" and "Tuhfah ar-Raghibin". "The Law of the Light of the Simbur" is a book of laws that combine customary law and Islamic teachings. In addition, "Tuhfah ar-Raghibin" is also a guide made by ulama for the ruler in order to remain consistent in keeping the customs that are in harmony with the values of Islamic teachings and rectifying the customs that begin to deviate. The assertive and fair attitude of the leader in running the government, supported by wise scholars that are able to make Palembang transformed into an advanced multicultural city as well as the capital of the Maritime kingdom in the archipelago. Therefore, the existence of ancient texts needs to be reviewed comprehensively and integratively so as to inspire alternative solutions for sustainable nation-building.